Freedom, corruption and moral strategies - Uniyal, Ekta (New Delhi Virtuous Publications, 2017)
This book seeks to bridge the gap between the actual relation between the two premises, i.e. misuse of freedom and presence of corruption; and the prevalent speculative nature of various theories that seem to be the order of the day. The book titled (3z(BFreedom, Corruption and Moral Strategies - With Specific Reference to Aristotle and J.S. Mill(3y(B, aims to explore the views and philosophies of the two philosophers into the various strategies, moral and otherwise while seeking a balance between human freedom and the level of corruption; and further identify the individual, moral, administrative and judicial controls that can be exercised to prevent the spread of the virus of corruption.s
Keywords: Corruption; Moral Strategies; Administrative and judicial controls